Pengujian Senyawa Marker Sebagai Kontrol Kualitas Produk Fitofarmaka: Studi Kasus Pada Produk Fitofarmaka Kelas Terapi Kardiovaskular - Kurniawati, Farida; Risma Uli, Aan; Bodrorini, Nany (Eruditio : Indonesia Journal of Food and Drug Safety, 2023)
Quality control of phytopharmaceutical products becomes a priority because they are included in the National Health Insurance. Quality control is carried out through active compound determination in the product. Currently, testing methods for active compounds are in herbs or plant extracts, but none for products. Phytopharmaceutical products for cardiovascular system therapy class contain Apii graveolentis herba and Orthosiphomis staminei folium extracts. The research aims to develop analytical methods that are selective, accurate and reliable to assay the active compounds of sinensetin in product contains Apii graveolentis herba extract by TLC and apigenin in product contains Orthosiphomis staminei folium extract by LC-MS/MS. From the results, it is proven that both methods are valid and reliable with linearity, precision and accuracy values that meet the requirements. The linearity of sinensetin and apigenin has correlation coefficient values of 0.9972 and 0.9995, with residual deviation values (Vx0) of 4.0% and 1.7%. Good repeatability is represented by the low number of precision values. Sinensetin precision at a concentration of 91.83; 310.33; and 586.68 µg/g were 1.11; 0.61; and 1.50%, while the apigenin precision at a concentration of 5; 15; and 25 µg/g were 5.82; 4.36; and 2.32% respectively. Accuracy of sinensetin at a concentration of 100.24; 300.72; and 601.44 µg/g were 90.8 - 92.7%; 102.5 - 103.7%; and 96.5 - 99.2%, while the accuracy of apigenin at a concentration of 5; 15; and 25 µg/g were 81.58 - 91.57%; 86.71 - 93.76%; and 89.12 - 93.31 % respectively. The developed methods were sensitive with the limit of quantitation (LoQ) values for sinensetin and apigenin were 3.34 ng/g and 6.67 µg/g. The validated methods can be applied to determine sinensetin and apigenin in cardiovascular system therapy class phytopharmaceutical products.